The Functionalization of Forest Police In Combating Illegal Logging Based On The Principles of Swift, Simple, And Low-Cost Justice. - Anis Maftu Haturrizqi; Bambang Sugiri; Mohammad Hamidi Masykur (International Journal of Global Community, 2025)
This study examines the role of Forest Police in combating illegal logging in Indonesia, emphasizing the principles of swift, simple, and low-cost justice. In the context of increasing forest exploitation that threatens ecosystems, the effectiveness of law enforcement becomes crucial, especially as illegal logging activities have expanded beyond mere illegal cutting. This research employs a normative legal research method, utilizing both legislative and historical approaches. The findings indicate that the limited authority of the Forest Police to conduct independent investigations and their dependence on the regular police force hinder responses to legal violations. Therefore, reforms in the authority structure and capacity enhancement of the Forest Police are necessary to expedite case handling, improve inter-agency coordination, and ensure better protection of forest resources. This study also recommends the implementation of modern technology in forest monitoring and increasing public awareness regarding the importance of environmental protection. With these measures, it is hoped that law enforcement can become more effective and contribute to the sustainability of forest ecosystems in Indonesia.